Objeto de aprendizagem adaptativo no ensino da lógica booleana - Braga, Olivia Ramos Morais (2015)
Learning is a complex process involving many variables, including the environment, social context, educational methodologies, teachers and students knowledge, among others. Highlighting the diversity of students in this process, this work presents the development of an Adaptive Learning Object using techniques of Adaptive Hypermedia and Artificial Intelligence as well as its application in classrooms, in beginners undergraduate classes, as a case study. For this purpose, this case study focuses on the learning of Algebra and Boolean Logic concepts, which has direct application in various disciplines that belong to the curriculum of several courses, like Electrical Engineering, Computer Science, Technology in Computer Networks, Systems Analysis and Development, Telecommunications, among others. By pointing out the difficulty of learning in Boolean Algebra and Logic-based subjects, this work aims to provide an improvement of educational performance in heterogeneous classrooms. Since the learning process is a challenging, interactive and iterative activity that involves a variety of aspects, it is intended that the application of adaptive techniques to a Learning Object can facilitate the skills development process by students.